2004
DOI: 10.1093/ajcn/80.6.1611
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic biomarkers of increased oxidative stress and impaired methylation capacity in children with autism

Abstract: An increased vulnerability to oxidative stress and a decreased capacity for methylation may contribute to the development and clinical manifestation of autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
706
5
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 826 publications
(759 citation statements)
references
References 54 publications
36
706
5
12
Order By: Relevance
“…54,55 In addition, alternative practitioners have been discussing the theory that anti-oxidant pathways are insufficient in patients with autism. This relationship has been noted in the past, and evidence of a predisposition of insufficient glutathione or anti-oxidant reserves in autistic patients has been described by James et al 56,57 Chez 58 previously reported a similar insufficiency in antioxidant protection in patients diagnosed with variants of Landau-Kleffner and concurrent autistic features. Insufficient anti-oxidant protection may not be the initial cause, but rather an endpoint of chronic ongoing inflammation.…”
Section: Human Evidence Of Ongoing Atypical Inflammatory Responsesupporting
confidence: 52%
“…54,55 In addition, alternative practitioners have been discussing the theory that anti-oxidant pathways are insufficient in patients with autism. This relationship has been noted in the past, and evidence of a predisposition of insufficient glutathione or anti-oxidant reserves in autistic patients has been described by James et al 56,57 Chez 58 previously reported a similar insufficiency in antioxidant protection in patients diagnosed with variants of Landau-Kleffner and concurrent autistic features. Insufficient anti-oxidant protection may not be the initial cause, but rather an endpoint of chronic ongoing inflammation.…”
Section: Human Evidence Of Ongoing Atypical Inflammatory Responsesupporting
confidence: 52%
“…The transfer of methyl groups is an important reaction in this metabolic pathway, and some hypothesize that oxidative stress and toxicity are responsible for the neuronal insult involved in ASD. 126 Abnormal metabolic profiles and impaired methylation have been reported in some children with ASD, 127,128 although no behavioral correlations were investigated. There are no randomized controlled trials published regarding the efficacy of molecules in this pathway on symptoms of ASD.…”
Section: Biologically Based Practicesmentioning
confidence: 99%
“…The formulation of the cell danger hypothesis was based on the recognition that similar metabolic pathways were coordinately regulated as an adaptive response to cellular threat regardless of whether the perturbation was caused by a virus,15 a bacterium,16 genetic forms of mitochondrial disease,10 or neurodevelopmental disorders with complex gene–environment pathogenic mechanisms like autism 17. These metabolic pathways traced to mitochondria.…”
Section: Introductionmentioning
confidence: 99%